2014
DOI: 10.1038/cdd.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

A novel PPARγ2 modulator sLZIP controls the balance between adipogenesis and osteogenesis during mesenchymal stem cell differentiation

Abstract: Mesenchymal stem cells (MSCs), also known as multipotent stromal cells, are used in clinical trials. However, the use of MSCs for medical treatment of patients poses a potential problem due to the possibility of transdifferentiation into unwanted tissues. Disruption of the balance during MSC differentiation leads to obesity, skeletal fragility, and osteoporosis. Differentiation of MSCs into either adipocytes or osteoblasts is transcriptionally regulated by the two key transcription factors PPARc 2 and Runx2. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 28 publications
0
44
0
2
Order By: Relevance
“…When the adipogenic pathway is blocked, the MSC enters the osteogenic pathway, and vice versa (74,(92)(93)(94).…”
Section: Thy-1 Controls the Adipogenic Differentiation Of Mscs And Admentioning
confidence: 99%
“…When the adipogenic pathway is blocked, the MSC enters the osteogenic pathway, and vice versa (74,(92)(93)(94).…”
Section: Thy-1 Controls the Adipogenic Differentiation Of Mscs And Admentioning
confidence: 99%
“…To determine the regulatory mechanism of LZIP involved in transcriptional activation of APOA4, multiple constructions containing different lengths (aa 21273/+1, 2498/+1, 2315/+1, and 2195/+1) of the 59 flanking region of APOA4 coupled to luciferase reporter gene were generated. The binding sites of CREB, AP-1, and OCT-1 are known as the binding sites of LZIP and its isoform, small LZIP (sLZIP) (28)(29)(30). Results from luciferase assay showed that LZIP 1-220 could bind to the region between aa 2315 and 2195 (Fig.…”
Section: Lzip Transcriptionally Regulates Apoa4 Expressionmentioning
confidence: 99%
“…Commitment and differentiation of MSCs into a specific phenotype in vivo is postulated to be controlled by hormonal and local factors (paracrine/autocrine) regulating the expression and/or activity of master differentiation genes (32, 40). Research on MSCs differentiation in vitro showed that activation of PPARγ2 and C/EBPs match to the master transcription factors for adipogenic differentiation (4143), while Runx2 and osterix are required for osteogenic differentiation (44). PPARγ2 positively regulates adipocyte differentiation while acting as a dominant negative regulator of osteogenic differentiation (45, 46).…”
Section: Relationship Between the Osteo/adipogenic Processes The Obesmentioning
confidence: 99%